2020
DOI: 10.26559/mersinsbd.736812
|View full text |Cite
|
Sign up to set email alerts
|

Yaşlı bireylerin yaşlılığa uyum düzeyi ile sağlıklı yaşam biçimi davranışları arasındaki ilişkinin değerlendirilmesi

Abstract: Yaşlanma ile oluşan değişikliklerle birlikte kronik hastalıkların artması ve günlük aktivelerde bağımsızlığın giderek azalması nedeni ile yaşlılığa uyum güçlüğü yaşanabilmektedir. Yaşanan uyum sorunları bireylerin sağlıklı yaşam biçimi davranışlarını etkileyebilmektedir. Yapılan bu çalışmada, yaşlı bireylerin yaşlılığa uyum düzeyi ile sağlıklı yaşam biçimi davranışları arasındaki ilişkinin belirlenmesi amaçlanmıştır. Gereç ve yöntem: Tanımlayıcı-ilişki arayıcı nitelikteki bu çalışma, 8 Nisan-30 Eylül 2019 tari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
4
0
3
Order By: Relevance
“…The current study determined that single people had higher fear of COVID-19, while those who were married had high levels of adaptation to old age. The literature reported that single people experienced the fear of COVID-19 more than those who were married and had a lower level of psychological resilience (Kımter, 2020; Wang et al, 2020; Kunz & Minder, 2020; Yadav et al, 2020); it was determined that those who were married and lived with their spouse had higher levels of adaptation to old age (Kütmez Yılmaz, 2020; Kütmez Yılmaz & Kıl, 2020). These results tell us that the reason why the fear of COVID-19 is higher for the single elderly people than the married ones is because they do not have social support, and that living alone causes them to feel unsafe; the high level of adaptation of married elderly people to old age can be explained by the positive effect of social support provided by the spouse on the physical and psychosocial health of elderly individuals and their ability to cope with stressful life events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study determined that single people had higher fear of COVID-19, while those who were married had high levels of adaptation to old age. The literature reported that single people experienced the fear of COVID-19 more than those who were married and had a lower level of psychological resilience (Kımter, 2020; Wang et al, 2020; Kunz & Minder, 2020; Yadav et al, 2020); it was determined that those who were married and lived with their spouse had higher levels of adaptation to old age (Kütmez Yılmaz, 2020; Kütmez Yılmaz & Kıl, 2020). These results tell us that the reason why the fear of COVID-19 is higher for the single elderly people than the married ones is because they do not have social support, and that living alone causes them to feel unsafe; the high level of adaptation of married elderly people to old age can be explained by the positive effect of social support provided by the spouse on the physical and psychosocial health of elderly individuals and their ability to cope with stressful life events.…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that the average ASADE score of the elderly individuals who participated in the study was 0.36 ± 0.32. The literature reported that the average ADEAS score ranged from 1.00 ± 0.68–1.07 ± 0.73 (Kütmez Yılmaz, 2020; Kütmez Yılmaz & Kıl, 2020; Şişman & Kutlu, 2016). Considering that the scale is scored between 0 and 3 and that adaptation increases as the scores approaches 0, the elderly individuals in the current study were found to have high levels of adaptation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sağlıklı yaşam biçimi, her bireyin sağlıklı davranışlar, dengeli beslenme, yeterli ve düzenli egzersiz vb. konularda sorumluluk almasını içermektedir (Yılmaz, 2020). Balcı ve ark.…”
Section: Araştırmanın Etik Yönüunclassified
“…(2020) İran'daki sosyoekonomik açıdan dezavantajlı yetişkinler arasında biraz daha yüksek zihinsel sağlık sorunu görüldüğünü bildirmişlerdir (Lam, Tyler, Scurrah, Reavley & Dite, 2019;Najafi ve ark., 2020). Yılmaz (2020) çalışmaya katılan yaşlı bireylerde gelir düzeyi arttıkça sağlıklı yaşam biçimi davranışlarının arttığını, Şimşek ve ark. (2012) ekonomik durum algısı yüksek olanların daha sağlıklı yaşam biçimi davranışına sahip olduklarını belirtmişlerdir (Yılmaz, 2020;Şimşek ve ark., 2012).…”
Section: Araştırmanın Etik Yönüunclassified
See 1 more Smart Citation